Other voices, other rooms? The relevance of dubbing in the reception of audiovisual products - González Ruiz, Víctor M.; Cruz García, Laura (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Unlike subtitling, the process of dubbing does not give the audience the opportunity to fully perceive the cultural gap between what they hear and see, and their own reality. This takes on a new dimension when the customs and the characters which are being depicted in the foreign film are not the ‘standard’ ones (i. e. those from the US) but those belonging to ‘marginal’ cultures (e.g. European, African or Asian).Let us take the imaginary example of a Moroccan film in which a character representing an Arabic-speaking Tuareg, whose voice has been dubbed into Spanish, uses the same kind of perfect Castilian as audiences usually hear in the mouth of a New York police officer in an American series dubbed into Spanish. The cultural impact of a different language is supposedly lost when the dubbing makes all the voices sound the same.This paper will discuss the influence of dubbing on the audience ’s perception of a range of films in the context of Spain ’s film industry. We will offer an empirical study with the aim of identifying the elements which filmgoers use to situate a film, and even question whether (and to what extent) the process of dubbing effaces the cultural and national origin of a film. The conclusions drawn will contribute to the research on the reception of (audiovisual) translation.